The Great Escape? A Quantitative Evaluation of the Fed's Liquidity Facilities - Del Negro, Marco; Eggertsson, Gauti; Ferrero, Andrea; Kiyotaki, Nobuhiro (American Economic Review, 2017)
We introduce liquidity frictions into an otherwise standard DSGE model with nominal and real rigidities and ask: can a shock to the liquidity of private paper lead to a collapse in short-term nominal interest rates and a recession like the one associated with the 2008 US financial crisis? Once the nominal interest rate reaches the zero bound, what are the effects of interventions in which the government provides liquidity in exchange for illiquid private paper? We find that the effects of the liquidity shock can be large, and show some numerical examples in which the liquidity facilities of the Federal Reserve prevented a repeat of the Great Depression in the period 2008–2009. (JEL E13, E31, E43, E44, E52, E58, G01)